Analisis Keterkaitan Pengetahuan Kewirausahaan dan Efikasi Diri Terhadap Minat Berwirausaha Kelas XII SMA Negeri 1 Lamongan - kusumawati, natasya indah; Ghofur, Abd.; Kuswanto, Kuswanto (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2025)
This research is motivated by the fact that applying entrepreneurial spirit among high school students is still challenging, as they may not be mentally prepared for the entrepreneurial world. Developing this spirit requires high interest, fostered by entrepreneurial knowledge and self-efficacy. Students' strong interest in entrepreneurship encourages bravery, as they feel empowered to become successful entrepreneurs. This study aims to analyze the relationship between entrepreneurial knowledge and self-efficacy on the entrepreneurial interest of students at SMA Negeri 1 Lamongan. Using a quantitative descriptive approach with questionnaires, the study involved 78 students from grades XII 11 and XII 12. Data collection methods included observation, tests, and documentation. T-test results partially indicate that entrepreneurial knowledge has no significant effect on entrepreneurial interest, while self-efficacy has a positive and significant effect. F-test results simultaneously show that both entrepreneurial knowledge and self-efficacy significantly influence entrepreneurial interest among class XII students at SMA Negeri 1 Lamongan.